A educação a distância e a formação continuada de professores de matemática: contribuições de um contexto formativo para a base de conhecimento docente - Pereira, Rudolph dos Santos Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The results presented by the National Basic Education Evaluation System, by the International Program of Students Assessment, and by the High School National Exam indicate that Brazilian students have a low proficiency level in mathematics: they are able to perform basic mathematical operations and the reading and interpretation of simple graphs. These markers point to the need for changes in the Maths teaching and learning processes in the Basic Education which can be started with the teacher’s action, searching for alternatives to help him/her in the classroom activities. Taking that into consideration, this research aims at investigating the contributions given by Distance Learning, as a training context, in a Maths teacher continuing training course, with Mathematical Modeling activities, for the manifestation and development of knowledge and teaching knowledge. For the development of this research, the theoretical framework adopted was the one based on teacher training in the pedagogical alternative of the Mathematical Modeling, as well as the guidelines of the Distance Learning. The methodological procedures that guided the research were based on the concepts of qualitative research. In the course planning, tools offered by the Distance Learning process were considered for the communication between course takers and the researcher, material availability and activities performance. The implementation and development of the Continuing Training of Maths Teachers course at service in the Basic Education took place in the virtual learning environment known as Moodle. The course was offered in the distance mode, semi-distance learning, lasting a hundred hours, split in three modules in which modeling activities were performed. Six course takers took part in the project. The data collection was done by the following tools: chat, forum, daily logs and tasks (reflective memorials) where expressions and reflections by the course takers were registered during the length of the continuing training course. The Discursive Textual Analysis was adopted for the collected data analysis, which allowed for the interpretation and comprehension of the registrations made by the course takers. Hence, from the discursive textual analysis performed in the data considered in this doctoral dissertation, it was possible to conclude that distance learning, understood as a possible context for continuing teacher training, boosted the manifestation and development of knowledge and teaching knowledge, by the course takers who took part in the research, allowing, among other things, the development of the autonomy of these teachers by means of the activities proposed in the held course, leading them to look for solutions for the personal difficulties faced by each one of them.

Os resultados apresentados pelo Sistema Nacional de Avaliação da Educação Básica, pelo Programa Internacional de Avaliação de Alunos e pelo Exame Nacional do Ensino Médio indicam que os alunos brasileiros possuem nível de proficiência baixo na disciplina de Matemática sendo capazes de realizar operações matemáticas básicas e a leitura e interpretação de gráficos simples. Esses indicadores apontam a necessidade de mudanças nos processos de ensino e de aprendizagem de Matemática na Educação Básica que podem iniciar com a atuação do professor, buscando alternativas para auxiliá-lo no ensino em sala de aula. Diante destas considerações, esta pesquisa visa investigar as contribuições da Educação a Distância, enquanto contexto formativo, em um curso de formação continuada de professores de Matemática, com atividades de Modelagem Matemática, para a manifestação e o desenvolvimento de conhecimentos e saberes da docência. No desenvolvimento da pesquisa foram adotadas as ações pautadas pelos referenciais teóricos da formação de professores, da alternativa pedagógica de Modelagem Matemática, bem como nas orientações da Educação a Distância. Os procedimentos metodológicos que nortearam a pesquisa foram pautados nos conceitos da pesquisa qualitativa. Na elaboração do curso consideramos as ferramentas ofertadas pela EaD para a comunicação entre os cursistas e o pesquisador, disponibilização de material e realização de atividades. A implementação e o desenvolvimento do curso de formação continuada de professores de Matemática em serviço na Educação Básica, ocorreu por meio do ambiente virtual de aprendizagem Moodle. O curso foi realizado na modalidade a distância, na forma semipresencial, com duração de cem horas, dividido em três módulos nos quais foram realizadas atividades de modelagem, e contou com a participação de seis cursistas. A coleta dos dados foi realizada pelas ferramentas de chat, fórum, diários e tarefas (memoriais reflexivos) onde eram registradas as expressões e reflexões dos cursistas durante o período de realização do curso de formação continuada. Para análise dos dados coletados, optamos pela Análise Textual Discursiva, que permitiu a interpretação e a compreensão dos registros efetuados pelos cursistas. Assim, a partir da análise textual discursiva realizada nos dados considerados nesta tese, foi possível evidenciar que a Educação a Distância, entendida como um contexto possível para a formação continuada de professores, favoreceu a manifestação e o desenvolvimento de conhecimentos e saberes da docência, por parte dos cursistas que participaram da pesquisa, permitindo, entre outras coisas, o desenvolvimento da autonomia desses docentes mediante às atividades propostas no curso realizado, levando-os a buscar soluções para as dificuldades pessoais encontradas pelos mesmos.
Distance learning and the continuing training of maths teachers: contributions of a training context as the basis for teaching knowledge
Keywords: Semi-distance learning; Mathematical modeling; Continuing training at service; Discursive textual analysis; Formação em serviço; Ensino semipresencial; Modelagem matemática; Análise textual discursiva